2009
DOI: 10.1016/j.biortech.2009.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Assessing amendment properties of digestate by studying the organic matter composition and the degree of biological stability during the anaerobic digestion of the organic fraction of MSW

Abstract: a b s t r a c tThe transformation of organic matter during anaerobic digestion of mixtures of energetic crops, cow slurry, agro-industrial waste and organic fraction of municipal solid waste (OFMSW) was studied by analysing different samples at diverse points during the anaerobic digestion process in a full-scale plant. Both chemical (fiber analysis) and spectroscopic approaches ( 13 C CPMAS NMR) indicated the anaerobic digestion process proceeded by degradation of more labile fraction (e.g. carbohydrate-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
109
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(133 citation statements)
references
References 17 publications
10
109
0
1
Order By: Relevance
“…As expected from the literature, the biogas digestates differed in their physical and chemical properties from the cattle slurries. In the present study, the biogas digestates had narrower C : N ratios (see also, e.g., Tambone et al, 2009), higher pH values (see also Wulf et al, 2002b andQuakernack et al, 2011), wider NH We observed an unexpected small change in the NH + 4 content of the soil immediately after fertilizer application, which can be attributed to different reasons. Firstly, the fertilizers partly remained on the plant canopy after splash plate application and therefore soil contact and infiltration were limited (Quakernack et al, 2011).…”
Section: Drainage and Fertilizer Effects On N-availability And N-transupporting
confidence: 58%
“…As expected from the literature, the biogas digestates differed in their physical and chemical properties from the cattle slurries. In the present study, the biogas digestates had narrower C : N ratios (see also, e.g., Tambone et al, 2009), higher pH values (see also Wulf et al, 2002b andQuakernack et al, 2011), wider NH We observed an unexpected small change in the NH + 4 content of the soil immediately after fertilizer application, which can be attributed to different reasons. Firstly, the fertilizers partly remained on the plant canopy after splash plate application and therefore soil contact and infiltration were limited (Quakernack et al, 2011).…”
Section: Drainage and Fertilizer Effects On N-availability And N-transupporting
confidence: 58%
“…−15 % absolute) and an enrichment in thermostable compounds in the range of 32 to 625 %, an increase of the degree of aromaticity (e.g., aromatic lignin by approx. 30-60 %), and an accumulation of long-chain aliphatic components due to the inability of the organisms involved in the digestion process to degrade these kind of materials under anoxic conditions (Table 1), indicating a relative increase of the biological recalcitrance in the digestates compared to the input materials (Cuetos et al 2009;Gómez et al 2005Gómez et al , 2007aGómez et al , b, 2011Marcato et al 2009;Pognani et al 2009;Tambone et al 2009Tambone et al , 2013 by unilateral decomposition of the easier decomposable C compounds. Similar conclusions have been drawn in many other reports by application of soil incubation approaches (e.g., Reinhold et al 1991;Sánchez et al 2008;Thomsen et al 2013).…”
Section: Effects Of Anaerobic Digestion On Digestate Organic Matter Cmentioning
confidence: 99%
“…The higher the obtained degradation of the feedstocks, the higher the relative increase of recalcitrance, as a consequence of the preferential degradation of easy degradable compounds in anaerobic digesters. The degree of increase of stable compounds corresponds to the degree of degradation obtained via anaerobic digestion (Asmus et al 1988;Gómez et al 2007a;Thomsen et al 2013) and with the decrease of the biological oxygen demand after field application of the manures Tambone et al 2009;Alburquerque et al 2012a). Characterizations of the C org compounds of digestates by FTIR spectra indicated that anaerobic stabilization of organic matter is mainly due to the buildup of more stable compounds in the dry matter rather than humification processes (Marcato et al 2009).…”
Section: Effects Of Anaerobic Digestion On Digestate Organic Matter Cmentioning
confidence: 99%
“…Biogas is already effectively used to produce electricity and heat, and to feed gas networks (Bekkering et al, 2010;Esposito et al, 2012). A further source of income produced by the process of methane fermentation of organic solids is represented by the semi-solid by-product of this process -post-fermentation sludge -that thanks to its high content of nutrients can be used in agriculture directly as a fertilizer or processed into compost to increase its quality (Esposito et al, 2012;Rehl and Müller, 2011;Tambone et al, 2009). Unfortunately, methane fermentation process has substantial drawbacks.…”
Section: Introductionmentioning
confidence: 99%